Penerapan pembelajaran blended learning pada mata pelajaran geografi di SMAN 1 Karangbinangun - Syah, Muhammad Ferdian (Maliki Interdisciplinary Journal, 2024)
Changes in conditions from pandemic to endemic will greatly affect various sectors of life, especially the world of education. With that, learning must be immediately prepared to face the endemic period. One way is to do this by implementing blended learning. The aim of this research was to determine the implementation of blended learning at SMAN 1 Karangbinangun. The results of this study indicate that learning conducted at SMAN 1 Karangbinangun has been directed to blended learning due to the ineffectiveness of full online learning.